PENGARUH TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR ILMU PENGETAHUAN ALAM KELAS V SEKOLAH DASAR - Wulandari, Dewinda; Kresnadi, Hery; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyse the effect  of model Teams Games Tourgames in the learning of Science against the results of the learning learners class fifth grade ofNortht Pontianak Elementary school 25. The method used is an experiment with the form of a Quasi Experimental Design draft non equivalent control group design. The population of the entire learners from two classes totalling 46 people, the sample of this research is the learners class VB totalling 23 persons as class experiments and learners as a class VA class a control that add up to 23 people. Data collection techniques used are measurement techniques and data-collecting instrument is the written test multiple choice-shaped.  Based on the analysis of data obtained average results post-test class experiment 77,11 and average post-test control of 73.37. Hypothesis test results using a t-test (Polled Variance) thitung = 1,989 obtained as for dk (23 + 23-2 = 44) with significant level α = 5% obtained ttabel = 1.676. The calcullation result show that thitung 1,989 > ttabel 1,676  Ha is accepted. That is, learning to use model Teams Games Tournamentin the learning Sciences learning outcomes. Based on the results of the calculation of effect size (ES) getting ES = 0.45 which includes secondary criteria. Keywords: Effect, Teams Games Tournament,Science, Results.